The urgency of hope in a time of despair. Issue 1 (June 2023) - Freeman, Mark
Given the state of the world, it is perilously easy—for some, including, at times, the author—to fall prey to despair, including the supposition that the world is moving inexorably downward, perhaps even toward some cataclysmic end. Alluring though despair may sometimes be, and impertinent though hope may sometimes seem, it is precisely in a time of despair that hope becomes most urgent. To succumb to despair is not only fatalistic but problematically "safe." Hope, predicated as it is on uncertainty about the future, is decidedly more risky. Difficult though it may be to fully embrace hope, it is imperative to hold on to it, for only then can a sense of the possible be sustained.